Mitochondrial Dysfunction and Oxidative Stress Caused by Cryopreservation in Reproductive Cells - Roberto Gualtieri; Guruprasad Kalthur; Vincenza Barbato; Maddalena Di Nardo; Satish Kumar Adiga; Riccardo Talevi (Antioxidants, 2021)
Mitochondria, fundamental organelles in cell metabolism, and ATP synthesis are responsible for generating reactive oxygen species (ROS), calcium homeostasis, and cell death. Mitochondria produce most ROS, and when levels exceed the antioxidant defenses, oxidative stress (OS) is generated. These changes may eventually impair the electron transport chain, resulting in decreased ATP synthesis, increased ROS production, altered mitochondrial membrane permeability, and disruption of calcium homeostasis. Mitochondria play a key role in the gamete competence to facilitate normal embryo development. However, iatrogenic factors in assisted reproductive technologies (ART) may affect their functional competence, leading to an abnormal reproductive outcome. Cryopreservation, a fundamental technology in ART, may compromise mitochondrial function leading to elevated intracellular OS that decreases sperm and oocytes’ competence and the dynamics of fertilization and embryo development. This article aims to review the role played by mitochondria and ROS in sperm and oocyte function and the close, biunivocal relationships between mitochondrial damage and ROS generation during cryopreservation of gametes and gonadal tissues in different species. Based on current literature, we propose tentative hypothesis of mechanisms involved in cryopreservation-associated mitochondrial dysfunction in gametes, and discuss the role played by antioxidants and other agents to retain the competence of cryopreserved reproductive cells and tissues.